A method for preparing a gradient structure biomedical hydrogel

Through layered casting and molding technology based on the principle of phase separation, precursor liquid with different DMSO contents are used for layered injection molding and low-temperature molding, the existing problems of complex, high cost and biological toxicity of gradient structure hydrogel preparation methods are solved, and the preparation of gradient structure hydrogels is realized, with the characteristics of stable structure and high mechanical properties.

CN119264508BActive Publication Date: 2025-05-02SUN YAT SEN UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411316484.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-05-02
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing preparation methods for gradient structure porous hydrogels have catalyst-assisted crosslinking, resulting in complex production systems, high cost, cumbersome processes, and often have potential biological toxicity problems, low physical crosslinking strength, low mechanical reliability, and easy structure collapse in complex mechanical environments.

Method used

The layered casting molding technology based on the phase separation principle is adopted to achieve the gradient structure formation of the hydrogel through layered injection molding and low-temperature molding of the precursor liquid of the dense layer and loose layer. The volume fraction of DMSO in the dense layer precursor liquid is more than 50%, and the volume fraction of DMSO in the loose layer precursor liquid is less than 50%. Phase separation and micro-domain crystallization are achieved through the difference in solvent composition between DMSO and water, and gelation is induced.

Benefits of technology

The preparation of gradient structure hydrogels has been realized, with the characteristics of stable structure and high mechanical properties. They are suitable for biomedicine and information science fields, and are simple in process and have no potential biotoxic risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005052358190000011
    Figure HDA0005052358190000011
  • Figure HDA0005052358190000012
    Figure HDA0005052358190000012
  • Figure HDA0005052358190000021
    Figure HDA0005052358190000021
Patent Text Reader

Abstract

The present invention relates to the field of medical materials, specifically a gradient structure hydrogel and its preparation method and medical products. The present invention uses DMSO aqueous solution of different concentrations as solvent and PVA as solute, and constructs a diffusion system by layered injection molding with different precursor solutions, so that the concentration transition zone presents a gel material with gradient changes in PVA microcrystal density, crosslinking degree, and gel product pore size along the thickness direction; the components in the concentration transition zone are gelled in situ, and the microstructure of the material is interlocked at the microscopic level without obvious interlayer interfaces. The present invention can also achieve material microstructure regulation of the upper surface and lower surface near the surface on the above basis by changing the ratio of PVA, DMSO and water in the dense layer precursor solution and the loose layer precursor solution, the duration of the low temperature process, and the duration of the aging treatment, so as to obtain material organizations with different microstructures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical materials, and specifically to a gradient structure hydrogel and a preparation method and a medical product thereof. Background Art

[0002] Gradient structured porous hydrogels have different microstructures and macroscopic properties in the spatial dimension, and have extremely rich application scenarios in the fields of biomedicine, information science, etc. In terms of biological efficacy, the gradient structure in this type of hydrogel can produce a spatial induction effect on cells, and regulate cell behavior by shaping the biomechanical and spatial environment around the cells. From the perspective of material mechanics, this type of gradient structure can make the material have gradually changing mechanical properties in space. Under appropriate debugging methods, material properties that match the human body can be obtained, and can be used for the repair of the junction of human soft and hard tissues. Based on the needs of the field of information science, the loose pore layer of this type of gradient structured porous hydrogel has extremely sensitive mechanical perception capabilities, while the dense layer can ensure the overall mechanical strength of the material, so it is very suitable for the preparation of various soft material sensors.

[0003] From the perspective of material appearance, porous hydrogels with gradient structures can be regarded as hydrogels with different pore sizes in one or several directions. Generally speaking, the realization of gradient pore size can be achieved by changing the degree of cross-linking. Some researchers have achieved the preparation of gradient structures by combining different types of cross-linking methods and achieving different proportions of different cross-linking methods in space. The common preparation method for porous hydrogels with gradient cross-linked structures is chemical cross-linking, that is, on the basis of achieving changes in the spatial concentration of the precursor solution, covalent bonds are formed within or between molecules to form a cross-linked network.

[0004] For example, Xue Bin and others from the Shenzhen Research Institute of Nanjing University disclosed an invention patent entitled "A new type of gradient hydrogel material, its preparation method and application" (CN112126083A), using multi-arm superhydrophilic polymers, polypeptide ligand molecules, linear polymers and metal ions to prepare a hydrogel material with both covalent bonds and coordination bonds, and the preparation of gradient hydrogel materials was achieved by changing the spatial distribution of covalent bonds and coordination bonds. Some researchers first preformed the precursor liquid, and then obtained a gel with a structural gradient change by unidirectional solution penetration; Huang Yan and others from Fuzhou University disclosed an invention patent entitled "A gradient structure protein hydrogel and its preparation method" (CN111072999A), by soaking the preformed protein hydrogel in a dodecyltrimethylammonium bromide solution to form a gradient structure with a dense outer shell and a loose, porous or even hollow interior. The above examples all belong to the preparation of porous hydrogels with gradient cross-linked structures by chemical cross-linking method. However, although chemical cross-linking has high strength and strong mechanical reliability, it often requires catalyst-assisted cross-linking, and the preparation system is complex, costly, and cumbersome, and often has potential biological toxicity.

[0005] Gradient porous structure hydrogels can also be realized by conventional physical cross-linking. The cross-linking method is to achieve cross-linking through non-covalent bonds such as intermolecular forces, but the cross-linking strength is low and the mechanical reliability is low. The gel has a greater risk of structural collapse under complex mechanical environments. For example, the conventional layered casting method, but this method often forms interlayer interfaces with sudden changes in structure and performance between different layers, which is not conducive to maintaining the stability of the material under complex mechanical conditions. Another example is the method of preparing gradient cross-linked hydrogels by solvent replacement. This is a new method for preparing hydrogels based on the principle of phase separation in recent years. Phase separation refers to a process in which the distribution state of the solute in a uniform dissolution system changes due to changes in external conditions (temperature, pressure, pH value, etc.), until it leaves the dissolved state and independently forms a new phase. By adjusting the solvent replacement strength, a gel with a gradient change in structure and morphology can be obtained in the dissolution system.

[0006] However, the existing solvent replacement method for preparing gradient cross-linked hydrogels only relies on the passive diffusion of poor solvents such as water, and has not yet involved improvements and designs based on solvent components. Therefore, the morphology of the obtained materials is often relatively fixed. In summary, the essence of physical cross-linking methods, including solvent replacement methods, is a phase separation problem. For polymer solution systems, due to the entanglement and kinking between polymer chains, the phase separation process often has a time lag, that is, a relaxation phenomenon. However, there are few reports on the discussion of relaxation issues in current related molding methods. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is a gradient structure hydrogel and its preparation method and medical product. The preparation method provided by the present invention can prepare a hydrogel with a gradient structure, the upper and lower surfaces have different microstructures, the structure is stable, and the mechanical properties are high. It can have extremely rich application scenarios in the fields of biomedicine, information science, etc.

[0008] The present invention provides a method for preparing a gradient structure hydrogel, comprising the following steps:

[0009] S1) dissolving the dense layer precursor solution in the loose layer precursor solution to obtain a preformed hydrogel;

[0010] The dense layer precursor solution and the loose layer precursor solution independently include PVA, DMSO and water;

[0011] The volume fraction of DMSO in the dense layer precursor solution is greater than 50% and less than 100%;

[0012] The volume fraction of DMSO in the loose layer precursor solution is greater than 0 and less than 50%;

[0013] S2) freezing the preformed hydrogel obtained in step S1) to obtain a gradient structure hydrogel.

[0014] The preparation method of the gradient structure hydrogel provided in this application is a layered casting molding technology based on the phase separation principle, which realizes the interlocking of structures of different scales between the casting layers. Compared with traditional physical cross-linking, the present invention can effectively increase the structural stability, improve the mechanical properties of the material, and ensure the service strength of the material in a complex mechanical environment.

[0015] The present invention first dissolves the loose layer precursor liquid on the dense layer precursor liquid to obtain a preformed hydrogel. Specifically, the dense layer precursor liquid is first injected into a mold, and then the loose layer precursor liquid is injected into the mold, so that the loose layer precursor liquid is maintained above the dense layer precursor liquid and is dissolved with the dense layer precursor liquid to obtain a preformed hydrogel.

[0016] The dense layer precursor solution and the loose layer precursor solution of the present invention both include polyvinyl alcohol (PVA), dimethyl sulfoxide (DMSO) and water, wherein PVA is used as a solute, DMSO and water are used as solvents, DMSO is a dominant organic solvent, and water is an inferior solvent. The mass percentage of PVA in the dense layer precursor solution of the present invention is 9wt% to 11wt%, preferably 10wt%; the mass percentage of PVA in the loose layer precursor solution is 4wt% to 6wt%, preferably 5wt%. The present invention utilizes the difference in solubility of the solute in the dominant solvent and the inferior solvent to achieve phase separation leading to micro-region crystallization and induced gelation; at the same time, the concentration difference of the solute in the loose layer and the dense layer is utilized to achieve passive diffusion of the solute between the two casting layers, thereby achieving structural interlocking of different scales.

[0017] The dense layer precursor solution and the loose layer precursor solution of the present invention preferably both include PVA, DMSO and water. PVA has been proven to be non-biotoxic and degradable in the natural environment, and is green and safe; DMSO is a low-toxic organic solvent, but its content can be reduced to a biosafety level after sufficient washing.

[0018] The volume fraction of DMSO in the dense layer precursor solution of the present invention is greater than 50% and less than 100%; the volume fraction of DMSO in the loose layer precursor solution is greater than 0 and less than 50%. Preferably, the volume fraction of DMSO in the dense layer precursor solution of the present invention is 60% to 80%; the volume fraction of DMSO in the loose layer precursor solution is 20% to 40%. In one embodiment of the present invention, the volume fraction of DMSO in the dense layer precursor solution is 80% and the volume fraction of DMSO in the loose layer precursor solution is 20%. In another embodiment of the present invention, the volume fraction of DMSO in the dense layer precursor solution is 60% and the volume fraction of DMSO in the loose layer precursor solution is 40%.

[0019] The dense layer precursor solution and the loose layer precursor solution of the present invention are both obtained by mixing PVA, DMSO and water. Specifically, PVA, DMSO and water are mixed and vacuum defoamed to obtain. More specifically, DMSO and water are mixed, and then PVA is added thereto, stirred at 90-100°C until PVA is completely dissolved, and then vacuum defoamed to obtain. The dense layer precursor solution and the loose layer precursor solution of the present invention are the same as those described above. The PVA, DMSO and water are proportioned according to the PVA mass percentage content and DMSO volume fraction of the dense layer precursor solution to obtain the dense layer precursor solution, and the PVA, DMSO and water are proportioned according to the PVA mass percentage content and DMSO volume fraction of the loose layer precursor solution to obtain the loose layer precursor solution. The PVA described in the present invention is any one or more of all polymerization degrees and alcoholysis degrees.

[0020] The dense layer precursor liquid of the present invention eventually forms a dense layer in a gradient hydrogel product, and the loose layer precursor liquid eventually forms a loose layer in a gradient hydrogel product. The loose layer precursor liquid and the dense layer precursor liquid have different densities, so the two liquids diffuse gradiently at the interface. The PVA dissolved in the DMSO-water solution will produce a large number of microscopic crystal regions due to the phase separation effect, thereby inducing in-situ gelation. The volume ratio of the dense layer precursor liquid and the loose layer precursor liquid of the present invention is 4.5: (1 to 2), preferably 4.5: 1.5. The time for mutual dissolution of the present invention is 1h to 2h, and the temperature for mutual dissolution is room temperature, specifically 20°C to 30°C.

[0021] After obtaining the preformed hydrogel, the preformed hydrogel is frozen to obtain a gradient structure hydrogel. Specifically, the preformed hydrogel is placed in a low temperature environment for freezing and gelling. The freezing and gelling temperature of the present invention is below 4°C, preferably -30°C to 4°C, and more preferably -20°C to 4°C. The freezing and gelling time of the present invention is 10h to 14h, preferably 11h to 13h. In the present invention, even if the concentration of PVA-DMSO-H2O in the diffusion zone exceeds the phase separation point (i.e., thermodynamically feasible), this process often progresses slowly. Therefore, by lowering the ambient temperature, a supercooling degree is provided for the phase separation process, the kinetic parameters of the phase change are optimized, and the molding of the material is promoted. Considering that the gelling temperature of PVA-DMSO in the dissolution system is about 4°C, the maximum temperature of low-temperature molding is specified to be 4°C; in actual operation, a -20°C refrigerator is often used to achieve a low-temperature molding environment, and the equipment requirements are simple and conducive to industrial production.

[0022] In certain embodiments of the present invention, after the preformed hydrogel is freeze-gelled to obtain a gradient structure hydrogel, the present invention further includes subjecting the gelled hydrogel to an aging treatment, and then washing, freeze-drying and rehydrating the hydrogel to obtain a gradient structure hydrogel; or directly washing, freeze-drying and rehydrating the gelled hydrogel. The phase separation process of the macromolecular system is often affected by the interaction between the macromolecules in the macromolecular dissolution system and exhibits a time lag. The gelled product is placed at room temperature for an aging treatment to give the gel material sufficient time to undergo a relaxation process, thereby enabling the gel material to achieve a more thorough phase separation process, and the aging treatment further stabilizes the microstructure of the material and improves its deformation resistance. In addition, washing and freeze-drying can also reduce the content of toxic DMSO in the gelled hydrogel to a biosafety level;

[0023] On the one hand, the present invention can perform aging treatment on the gelled product, and then wash, freeze-dry and rehydrate it to obtain a gradient structure hydrogel. The aging treatment specifically involves placing the gelled product at room temperature for a period of time, and the room temperature is specifically 20 to 30°C. The aging treatment time of the present invention is not less than 1 hour, specifically 1 hour to 4 days; in certain embodiments of the present invention, the aging treatment time is 3 to 4 days. The washing specifically involves washing the aging-treated hydrogel with excess pure water at a speed of 100 to 200 rpm, replacing the pure water every 25 to 35 minutes, and repeating the washing 5 to 7 times, preferably washing at a speed of 150 rpm, replacing the pure water every 30 minutes, and repeating the washing 6 times. After the washing is completed, it is considered that DMSO is washed to a trace amount of residue by pure water, and the volume ratio of the aging-treated hydrogel to the excess pure water is 1: (9 to 11), preferably 1: 10. The freeze-drying specifically involves pre-freezing the washed hydrogel so that it is completely frozen. The pre-freezing temperature and time are not particularly limited, as long as the washed hydrogel is completely frozen. The completely pre-frozen hydrogel sample is placed in a freeze dryer, the freezing temperature is maintained below -50°C, and freeze-dried for 20 to 25 hours, preferably lyophilized for 24 hours; when the sample appears white and opaque, it is considered that DMSO has been completely removed. The rehydration specifically involves placing the freeze-dried hydrogel in an excess of 0.01 to 0.02 mol / L PBS buffer for 20 to 25 hours, preferably placing it in an excess of 0.01 mol / L PBS buffer for 24 hours. The volume ratio of the freeze-dried hydrogel to the PBS buffer is 1:(9 to 11), preferably 1:10.

[0024] In another aspect of the present invention, the gelled product can be directly washed, freeze-dried and rehydrated to obtain a gradient structure hydrogel. The washing, freeze-drying and rehydration are the same as those described above and will not be described in detail.

[0025] The present invention also provides a gradient structure hydrogel obtained by the preparation method described in any of the above technical solutions. The gradient structure hydrogel provided by the present invention has different microstructures on the upper and lower surfaces, stable structure, high mechanical properties, and can have extremely rich application scenarios in the fields of biomedicine, information science, etc. In certain embodiments of the present invention, the gradient structure hydrogel is a gradient structure medical hydrogel. The present invention also provides a medical product, which is composed of the gradient structure hydrogel obtained by the preparation method described in any of the above technical solutions.

[0026] The present invention provides a gradient structure hydrogel and a preparation method and medical products thereof. The present invention uses DMSO aqueous solution of different concentrations as a solvent and PVA as a solute, and constructs a diffusion system by layered injection molding with different precursor solutions, so that the concentration transition zone presents a gel material with a gradient change in PVA microcrystal density, crosslinking degree, and gel product pore size along the thickness direction; the components in the concentration transition zone achieve in-situ gelation, and the microstructure of the material achieves interlocking at the microscopic level without obvious interlayer interfaces. The present invention can also achieve material microstructure regulation of the upper surface and the lower surface near the surface layer on the above basis by changing the ratio of PVA, DMSO and water of the dense layer precursor solution and the loose layer precursor solution, the duration of the low temperature process, and the duration of the aging treatment, and obtain material organizations with different microstructures. The preparation method provided by the present invention is based on the layered casting molding technology (essentially physical crosslinking) based on the phase separation principle to prepare a gradient structure hydrogel, with a simple process flow, a simple preparation system, and no potential biological toxicity risks. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of the preparation process of the gradient structure hydrogel of the present invention;

[0028] Figure 2 This is a SEM image of the loose porous layer of the hydrogel material obtained in Example 1 of the present invention;

[0029] Figure 3 This is a SEM image of the transition region of the hydrogel material obtained in Example 1 of the present invention;

[0030] Figure 4 This is a SEM image of the dense pore layer of the hydrogel material obtained in Example 1 of the present invention;

[0031] Figure 5 This is a SEM image of the loose pore layer of the hydrogel material obtained in Example 2 of the present invention;

[0032] Figure 6 This is a SEM image of the transition region of the hydrogel material obtained in Example 2 of the present invention;

[0033] Figure 7This is a SEM image of the dense pore layer of the hydrogel material obtained in Example 2 of the present invention;

[0034] Figure 8 This is a SEM image of the loose pore layer of the hydrogel material obtained in Comparative Example 1 of the present invention;

[0035] Fig. 9 This is a SEM image of the transition region of the hydrogel material obtained in Comparative Example 1 of the present invention;

[0036] Fig.10 This is a SEM image of the dense pore layer of the hydrogel material obtained in Comparative Example 1 of the present invention;

[0037] Fig.11 This is a SEM image of the loose pore layer of the hydrogel material obtained in Comparative Example 2 of the present invention;

[0038] Fig.12 This is a SEM image of the transition region of the hydrogel material obtained in Comparative Example 2 of the present invention;

[0039] Fig.13 This is a SEM image of the dense pore layer of the hydrogel material obtained in Comparative Example 2 of the present invention;

[0040] Fig.14 The figure is a graph showing the mechanical properties test results of the hydrogel materials obtained in the examples and comparative examples of the present invention. DETAILED DESCRIPTION

[0041] The present invention discloses a gradient structure hydrogel and a preparation method and a medical product thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0042] The hydrogel material with gradient structure of the present invention is prepared according to the steps of preparing precursor solution, layered casting, low temperature molding and aging treatment, and finally a finished product is obtained; in this process, after the precursor solution is layered cast, that is, injection molded, it is left standing at room temperature for 1 hour to allow the precursor solution to diffuse between layers to produce phase separation, and then placed at -20°C for 12 hours to complete gelation, and finally placed at room temperature for 4 days to complete phase separation. Figure 1 As shown, Figure 1 This is a schematic diagram of the preparation process of the gradient structure hydrogel of the present invention.

[0043] The PBS buffer solution of the present invention is prepared from PBS dry powder of solarbio, with a pH value of 7.2-7.4, and main components are sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium chloride.

[0044] The present invention will be further described below in conjunction with embodiments:

[0045] Example 1

[0046] Step A: Prepare the precursor solution of the dense layer by mixing 80 mL of dimethyl sulfoxide (DMSO) with 20 mL of deionized water to obtain a DMSO aqueous solution with a volume fraction of 80%. Then, add 10 g of polyvinyl alcohol (PVA) to the obtained DMSO aqueous solution, stir at 95°C until the PVA is completely dissolved, and perform vacuum degassing to obtain a colorless clear solution I;

[0047] Step B: Prepare the precursor solution of the loose layer by mixing 20 mL of dimethyl sulfoxide (DMSO) and 80 mL of deionized water in a certain proportion to obtain a 20% DMSO aqueous solution. Then, add 5 g of polyvinyl alcohol (PVA) to the obtained DMSO aqueous solution, stir at 95°C until the PVA is completely dissolved, and perform vacuum degassing to obtain a colorless clear solution II;

[0048] Step C: Slowly inject 4.5 mL of the colorless clear solution I obtained in step A into a 6 cm flat dish mold, and then slowly inject 1.5 mL of the colorless clear solution II obtained in step B into the 6 cm flat dish mold, so that it is maintained above the colorless clear solution I;

[0049] Step D: After the liquid surface returns to calm, it is considered that the interface of the two layers of colorless clear solution is mutually dissolved, and the preforming is completed by standing for 1 hour;

[0050] Step E: placing the preformed sample in a -20°C refrigerator for 12 hours to achieve gelation, thereby preparing a sheet-like hydrogel material with a gradient structure and a thickness of 0.9 mm to 1.0 mm;

[0051] Step F: The gelled sample was aged at room temperature for 4 days, and the hydrogel material after aging treatment was washed at a volume ratio of gelling agent: pure water = 1:10, specifically, it was washed on a shaker at a speed of 150rpm, and the pure water was replaced every 30 minutes, and washed 6 times. Then the washed hydrogel was placed in a -20℃ refrigerator for pre-freezing for 12 hours, and then placed in a freeze dryer, and the freezing temperature was kept below -50℃ for freeze drying for 24 hours, and then soaked in 0.01M PBS buffer for 24 hours at a volume ratio of gel: PBS buffer = 1:10 for rehydration, so as to further improve the performance of the obtained hydrogel material.

[0052] The microstructure of the hydrogel material obtained above was characterized. Figure 2 to Figure 4 As shown, Figure 2 This is a SEM image of the loose pore layer of the hydrogel material obtained in Example 1 of the present invention. Figure 3 This is a SEM image of the transition region of the hydrogel material obtained in Example 1 of the present invention. Figure 4 This is a SEM image of the dense pore layer of the hydrogel material obtained in Example 1 of the present invention.

[0053] Example 2

[0054] Compared with Example 1, the difference is:

[0055] The DMSO aqueous solution in step A is a 60% DMSO aqueous solution;

[0056] The DMSO aqueous solution in step B is a 40% DMSO aqueous solution.

[0057] The microstructure of the hydrogel material obtained above was characterized. Figure 5 to Figure 7 As shown, Figure 5 This is a SEM image of the loose pore layer of the hydrogel material obtained in Example 2 of the present invention. Figure 6 This is a SEM image of the transition region of the hydrogel material obtained in Example 2 of the present invention. Figure 7 This is a SEM image of the dense pore layer of the hydrogel material obtained in Example 2 of the present invention.

[0058] Comparative Example 1

[0059] Step A: Prepare a precursor solution for the dense layer, add 10 g of polyvinyl alcohol (PVA) to 100 mL of dimethyl sulfoxide, stir at 95° C. until the PVA is completely dissolved, and perform vacuum degassing to obtain a colorless clear solution I;

[0060] Step B: Slowly inject 6 mL of the colorless clear solution I obtained in step A into a 6 cm flat dish mold;

[0061] Step C: Pour 1L of pure water into a 3L beaker, and carefully place the plate from step B into the water and at the bottom of the beaker. Then use a glass rod to drain and inject another 2L of pure water along the wall of the cup. During this period, avoid turbulence that disturbs the PVA-DMSO solution in the plate from step B. After standing for 24 hours, take out the plate, demold the hydrogel sample therein, and prepare a sheet-like hydrogel material with a thickness of 0.9mm to 1.0mm. Wash, freeze-dry, and rehydrate the sample in the same manner as in Example 1 to obtain the final sample hydrogel material.

[0062] The microstructure of the hydrogel material obtained above was characterized. Figures 8 to 10 As shown, Figure 8 This is a SEM image of the loose pore layer of the hydrogel material obtained in Comparative Example 1 of the present invention. Fig. 9 This is a SEM image of the transition region of the hydrogel material obtained in Comparative Example 1 of the present invention. Fig.10 This is a SEM image of the dense pore layer of the hydrogel material obtained in Comparative Example 1 of the present invention.

[0063] Comparative Example 2

[0064] Step A: Prepare a precursor solution for the dense layer, add 10 g of polyvinyl alcohol (PVA) to 100 mL of dimethyl sulfoxide (equivalent to 100% DMSO volume fraction), stir at 95° C. until PVA is completely dissolved, and perform vacuum degassing to obtain a colorless clear solution I;

[0065] Step B: Prepare a precursor solution for the loose layer, add 5 g of polyvinyl alcohol (PVA) to 100 mL of deionized water (equivalent to DMSO volume fraction of 0), stir at 95° C. until PVA is completely dissolved, and perform vacuum degassing to obtain a colorless clear solution II;

[0066] Step C: Slowly inject 4.5 mL of the colorless clear solution I obtained in step A into a 6 cm flat dish mold, and then slowly inject 1.5 mL of the colorless clear solution II obtained in step B into the 6 cm flat dish mold, so that it is maintained above the colorless clear solution I;

[0067] Step D: After the liquid surface returns to calm, it is considered that the interface of the two layers of colorless clear solution is mutually dissolved, and the preforming is completed by standing for 1 hour;

[0068] Step E: placing the preformed sample in a -20°C refrigerator for 12 hours to achieve gelation, thereby preparing a sheet-like hydrogel material with a thickness of 0.9 mm to 1.0 mm;

[0069] Step F: According to the same method as step F of Example 1, the gelled sample is subjected to aging treatment at room temperature for 4 days, washed, freeze-dried and then rehydrated to further improve the performance of the obtained hydrogel material.

[0070] The microstructure of the hydrogel material obtained above was characterized. Figure 11 to Figure 13 As shown, Fig.11 This is a SEM image of the loose pore layer of the hydrogel material obtained in Comparative Example 2 of the present invention. Fig.12 This is a SEM image of the transition region of the hydrogel material obtained in Comparative Example 2 of the present invention. Fig.13 This is a SEM image of the dense pore layer of the hydrogel material obtained in Comparative Example 2 of the present invention.

[0071] The hydrogel materials obtained in the above examples and comparative examples were cut into I-shaped standard tensile specimens (test area size: 20×3 mm) for mechanical property testing. Fig.14 As shown, Fig.14 The figure is a graph showing the mechanical properties test results of the hydrogel materials obtained in the examples and comparative examples of the present invention.

[0072] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a gradient structure hydrogel, characterized in that: The following steps are involved: S1) dissolving the loose layer precursor solution in the dense layer precursor solution to obtain a preformed hydrogel; The dense layer precursor solution and the loose layer precursor solution independently include PVA, DMSO and water; The volume fraction of DMSO in the dense layer precursor solution is 60% to 80%; The volume fraction of DMSO in the loose layer precursor solution is 20% to 40%; S2) freezing the preformed hydrogel obtained in step S1) to obtain a gradient structure hydrogel.

2. The preparation method according to claim 1, characterized in that: In step S1), the mass percentage of PVA in the dense layer precursor solution is 9 wt% to 11 wt%; The mass percentage of PVA in the loose layer precursor solution is 4 wt% to 6 wt%.

3. The preparation method according to claim 1, characterized in that: In step S1), the volume ratio of the dense layer precursor solution to the loose layer precursor solution is 4.5:(1-2).

4. The preparation method according to claim 1, characterized in that: In step S1), the time for mutual dissolution is 1 h to 2 h.

5. The preparation method according to claim 1, characterized in that: In step S2), the freezing gelling temperature is below 4°C, and the freezing gelling time is 10 h to 14 h.

6. The preparation method according to any one of claims 1 to 5, characterized in that In step S2), after the freeze-gelling, the gelled product is subjected to aging treatment, followed by washing, freeze-drying and rehydration; the aging treatment temperature is 20°C to 30°C, and the aging treatment time is 1 h to 4 days.

7. The preparation method according to any one of claims 1 to 5, characterized in that In step S2), after freezing and gelling, the gelled product is washed, freeze-dried and rehydrated.

8. A gradient structure hydrogel obtained by the preparation method according to any one of claims 1 to 7.

9. A medical product, characterized in that The invention is composed of a gradient structure hydrogel obtained by the preparation method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Protein hydrogel with gradient structure and preparation method thereof

    CN111072999A

  • Novel gradient hydrogel material, and preparation method and application thereof

    CN112126083A

  • Preparation method of chitosan-based dressing with compact-loose double layer structure

    CN104740674A

  • Double-layer hydrogel with nano-silver loaded on surface and preparation method of double-layer hydrogel

    CN111514371A